Inclusive Digital Marketing For Urban Fashion Enterprises: The Roles Of Body Positivity, Micro-Influencers, And Brand Image - Pawitri, Ni Nyoman Herlina Maha; Junaedi, I Wayan Ruspendi; Utama, I Gusti Bagus Rai; Komalasari, Yeyen (PANGRIPTA, 2026)
The expansion of digital fashion markets offers new opportunities for urban creative enterprises, but it also requires marketing practices that are inclusive, credible, and responsive to changing consumer values. This study examines the roles of body positivity campaigns, micro-influencers, and brand image in shaping women consumers’ purchase intentions within Indonesia’s urban digital fashion market. Data were collected through an online survey involving 110 women aged 18–35 who actively used Instagram and TikTok and resided in selected urban market areas in Indonesia. The proposed relationships were examined using Partial Least Squares–Structural Equation Modeling. The findings reveal that body positivity campaigns contribute to a favorable brand image but do not directly translate into purchase intention. Micro-influencers play a more comprehensive role by contributing to both brand image and purchase intention. Brand image is also associated with stronger purchase intention and mediates the relationship between micro-influencers and purchase intention. However, it does not mediate the relationship between body positivity campaigns and purchase intention. These findings indicate that body positivity and micro-influencer communication operate through different marketing mechanisms. Inclusive messages primarily strengthen consumer perceptions of the brand, whereas credible micro-influencers help connect brand communication with purchasing interest. From an urban development perspective, the findings provide consumer-level evidence that can inform local government agencies, business incubators, and creative-economy stakeholders in designing digital marketing assistance, responsible influencer partnerships, and inclusive branding programs for urban fashion enterprises. This study contributes to the development of competitive, inclusive, and digitally adaptive urban creative-economy ecosystems.